Intravascular large B-cell lymphoma of the central nervous system with renal involvement: a case report and literature review - Li, Jun; Li, Zhaojiao; Shi, Yifeng; Chen, Jiajie; Zhao, Heng; Mao, Xueye; Li, Shan; Wang, Huiying; Meng, Qiang; Liu, Lingchun (Frontiers in Oncology, 2025)
Intravascular large B-cell lymphoma (IVLBCL) is a highly aggressive type of non-Hodgkin’s lymphoma. The clinical manifestations and imaging of this disease are nonspecific, making diagnosis challenging. We report a case of a patient with recurrent stroke-like symptoms, primarily characterized by hemiplegia, vertigo, ataxia, and proteinuria. Brain MRI revealed multiple cerebral infarctions, microbleeds, and meningeal enhancement. Ultimately, the patient was diagnosed with IVLBCL through a brain tissue biopsy, and involvement of the kidneys was suspected. We suggest considering IVLBCL in patients who present with recurrent stroke-like symptoms, fluctuating neurological deficits, the aforementioned MRI findings, and involvement of other organs. Additionally, central nervous system vasculitis(CNSV) may represent a transitional manifestation of the disease. Pathological biopsy is the gold standard for diagnosis. We hope that through this case, doctors can gain a deeper understanding of IVLBCL, enabling early diagnosis and timely treatment to improve prognosis.